2018
DOI: 10.1002/pnp.515
|View full text |Cite
|
Sign up to set email alerts
|

Eye drop psychosis in Parkinson's disease: a cautionary tale

Abstract: Anticholinergic agents are used in a number of conditions ranging from overactive bladder and bradycardia to travel sickness but side‐effects such as hallucinations, impaired memory and restlessness are increasingly recognised, though still under‐reported in clinical practice. In Parkinson's disease anticholinergics such as atropine are recommended by NICE for the management of excessive drooling. Dr Ferris et al. present such a case where commencing sublingual atropine drops caused a patient to develop hypera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Synthesized from 19c (0.090 g, 0.176 mmol) and acetone (3.5 mL, 0.05 M) using the general procedure for the synthesis of C6/C7 aziridines to afford 20c (0.085 g, >99%) as a brown solid that was used without further purification. 1 (1R,2R,4S,5S)-9-Methyl-3-phenyl-3,9-diazatricyclo[3.3.1.0 2,4 ]nonane (21a). Synthesized from 20a (0.059 g, 0.171 mmol, 1.0 equiv), hydrazine monohydrate (0.025 mL, 0.256 mmol, 1.5 equiv), Raney Ni (0.020 g, 0.342 mmol, 2.0 equiv), 37% CH 2 O (aq) (0.014 mL, 0.188 mmol, 1.1 equiv), and MeOH (1.7 mL, 0.1 M) following the general procedure for the deprotection-reduction-reductive amination sequence.…”
Section: Tert-butyl 5-((1r2s4r5s)-9-(13-dioxoisoindolin-2-yl)-39diaza...mentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesized from 19c (0.090 g, 0.176 mmol) and acetone (3.5 mL, 0.05 M) using the general procedure for the synthesis of C6/C7 aziridines to afford 20c (0.085 g, >99%) as a brown solid that was used without further purification. 1 (1R,2R,4S,5S)-9-Methyl-3-phenyl-3,9-diazatricyclo[3.3.1.0 2,4 ]nonane (21a). Synthesized from 20a (0.059 g, 0.171 mmol, 1.0 equiv), hydrazine monohydrate (0.025 mL, 0.256 mmol, 1.5 equiv), Raney Ni (0.020 g, 0.342 mmol, 2.0 equiv), 37% CH 2 O (aq) (0.014 mL, 0.188 mmol, 1.1 equiv), and MeOH (1.7 mL, 0.1 M) following the general procedure for the deprotection-reduction-reductive amination sequence.…”
Section: Tert-butyl 5-((1r2s4r5s)-9-(13-dioxoisoindolin-2-yl)-39diaza...mentioning
confidence: 99%
“…The product was purified by chromatography on silica gel using EtOAc/MeOH/NH 4 OH (9:1:0.1) to afford 21c (0.045 g, 71%) as a tan solid. 1 H NMR (400 MHz, CDCl 3 ): δ 7.96 (d, J = 7.5 Hz, 1H), 7.54 (d, J = 3.8 Hz, 1H), 7.12 (d, J = 2.3 Hz, 1H), 7.02 (dd, J = 8.8, 2.3 Hz, 1H), 6.45 (d, J = 3.8 Hz, 1H), 3.31 (s, 2H), 2.81 (s, 2H), 2.60 (s, 3H), 2.00−1.89 (m, 2H), 1.87−1.77 (m, 1H), 1.66 (s, 9H), 1.51−1.41 (m, 1H), 1.32 (dd, J = 13.2, 6.6 Hz, 2H) ppm; 13 tert-Butyl 4-((1R,2R,4S,5S)-9-Methyl-3,9-diazatricyclo[3.3.1.0 2,4 ]nonan-3-yl)-1H-indole-1-carboxylate (21d). Synthesized from 20d (0.100 g, 0.206 mmol, 1.0 equiv), hydrazine monohydrate (0.030 mL, 0.310 mmol, 1.5 equiv), Raney Ni (0.024 g, 0.412 mmol, 2.0 equiv), 37% CH 2 O (aq) (0.017 mL, 0.227 mmol, 1.1 equiv), and MeOH (2.0 mL, 0.1 M) following the general procedure for the deprotectionreduction-reductive amination sequence.…”
Section: Tert-butyl 5-((1r2s4r5s)-9-(13-dioxoisoindolin-2-yl)-39diaza...mentioning
confidence: 99%
“…Even though psychiatric side effects are rare with topical forms, still psychosis and delirium have been reported with them. [ 51 , 52 ] Central anticholinergic syndrome has also been described,[ 53 ] the manifestations of which include psychotic symptoms.…”
Section: Ophthalmic Drugs Causing Psychiatric Side Effectsmentioning
confidence: 99%
“…Physicians and caregivers should monitor patients treated with anticholinergic drugs for associated adverse side effects 95 (Box 3), which include urinary retention, blurred vision, hallucinations and confusion. 96 Patients with PD who have cognitive impairments are more susceptible to developing these side effects, 3 or increased Alzheimer's disease pathology.…”
Section: Pharmacological Therapies To Reduce or Prevent Sialorrhoeamentioning
confidence: 99%
“…Adverse events associated with anticholinergic drug treatment. 95 A patient with PD, reported that sialorrhoea was the symptom of their disease causing the majority of their concern, because they were unable to sit down to read the newspaper without experiencing severe sialorrhoea. After no response to nonpharmacological methods of management, off-label oral administration of atropine eye drops (10 mg/ml 0.5 ml per day) was trialled.…”
Section: Pharmacological Therapies To Reduce or Prevent Sialorrhoeamentioning
confidence: 99%